A Molecular Hybrid for Mitochondria‐Targeted NO Photodelivery. (30th November 2017) - Sodano, Federica; Gazzano, Elena; Fraix, Aurore; Rolando, Barbara; Lazzarato, Loretta; Russo, Marina; Blangetti, Marco; Riganti, Chiara; Fruttero, Roberta; Gasco, Alberto; Sortino, Salvatore
Abstract: The design, synthesis, spectroscopic and photochemical properties, and biological evaluation of a novel molecular hybrid that is able to deliver nitric oxide (NO) into mitochondria are reported. This molecular conjugate unites a tailored o ‐CF3 ‐ p ‐nitroaniline chromophore, for photo‐regulated NO release, and a rhodamine moiety, for mitochondria targeting, in the same molecular skeleton via an alkyl spacer. A combination of steady‐state and time‐resolved spectroscopic and photochemical experiments demonstrate that the two chromogenic units preserve their individual photophysical and photochemical properties in the conjugate quite well. Irradiation with violet light triggers NO release from the nitroaniline moiety and photoionization in the rhodamine center, which also retains considerable fluorescence efficiency. The molecular hybrid preferentially accumulates in the mitochondria of A549 lung adenocarcinoma cells where it induces toxicity at a concentration of 1 μm, exclusively upon irradiation. Comparative experiments, carried out with ad‐hoc‐synthesized model compounds, suggest that the phototoxicity observed at such a low concentration is probably not due to NO itself, but rather to the formation of the highly reactive peroxynitrite that is generated from the reaction of NO with the superoxide anion. Abstract : Just say NO to cancer : A novel molecular hybrid effectively localizes in the mitochondria of A549 lung adenocarcinoma cells and releases NO therein under the control of visible light irradiation. A combination of steady‐state and time‐resolved spectroscopic and photochemical experiments demonstrate that the two chromogenic units preserve their individual photophysical and photochemical properties in the conjugate quite well.